2019
DOI: 10.1080/22221751.2019.1637072
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus can be transmitted through the blood and produce infections in blood recipients: Evidence from two animal models

Abstract: Human papillomaviruses (HPV) contribute to most cervical cancers and are considered to be sexually transmitted. However, papillomaviruses are often found in cancers of internal organs, including the stomach, raising the question as to how the viruses gain access to these sites. A possible connection between blood transfusion and HPV-associated disease has not received much attention. Here we show, in rabbit and mouse models, that blood infected with papillomavirus yields infections at permissive sites with det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 59 publications
1
42
0
Order By: Relevance
“…showing that these viruses can produce infection via the bloodstream in some animal models appear to strengthen our suggestions (Cladel et al, 2019). Furthermore, it is believed that blood could be an actual route of HPV dissemination as the virus has been found…”
Section: Discussionsupporting
confidence: 82%
“…showing that these viruses can produce infection via the bloodstream in some animal models appear to strengthen our suggestions (Cladel et al, 2019). Furthermore, it is believed that blood could be an actual route of HPV dissemination as the virus has been found…”
Section: Discussionsupporting
confidence: 82%
“…Meanwhile, Sardh has been reported to reduce sarcosine levels and attenuate the invasion of DU145 prostate cancer cells ( Khan et al, 2013 ). Pgam2 is a crucial enzyme involved in glycolysis related to oxidative stress, and decreased expression of Pgam2 was observed in proliferative disease induced by local infections ( Cladel et al, 2019 ). In addition, clinical evidence has suggested that Sdsl has specific protein expression in peripheral cholangiocarcinoma ( Darby et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies used included rabbit anti-MmuPV1 L1 and E4 (developed in the lab, 1:200 for immunofluorescence), and mouse anti-HPV18, HPV-16 and MmuPV1 neutralising antibodies (which were a gift of Neil Christensen, Pennsylvania State University College of Medicine, 1:200 for neutralising assay) [21] , [22] , [23] .…”
Section: Methodsmentioning
confidence: 99%